The Cell Fate Controlling CLE40 Peptide Requires CNGCs to Trigger Highly Localized Ca2+ Transients in Arabidopsis thaliana Root Meristems - Breiden, Maike; Olsson, Vilde; Bluemke, Patrick; Schlegel, Jenia; Gustavo-Pinto, Karine; Dietrich, Petra; Butenko, Melinka A.; Simon, Ruediger (Plant and Cell Physiology, 2021)
Communication between plant cells and their biotic environment largely depends on the function of plasma membrane localized receptor-like kinases (RLKs). Major players in this communication within root meristems are secreted peptides, including CLAVATA3/EMBRYO SURROUNDING REGION40 (CLE40). In the distal root meristem, CLE40 acts through the RLK ARABIDOPSIS CRINKLY4 (ACR4) and the leucine-rich repeat (LRR) RLK CLAVATA1 (CLV1) to promote cell differentiation. In the proximal meristem, CLE40 signaling requires the LRR receptor-like protein CLAVATA2 (CLV2) and the membrane localized pseudokinase CORYNE (CRN) and serves to inhibit cell differentiation. The molecular components that act immediately downstream of the CLE40-activated receptors are not yet known. Here, we show that active CLE40 signaling triggers the release of intracellular Ca2+ leading to increased cytosolic Ca2+ concentration ([Ca2+](cyt)) in a small subset of proximal root meristem cells. This rise in [Ca2+]cyt depends on the CYCLIC NUCLEOTIDE GATED CHANNELS (CNGCs) 6 and 9 and on CLV1. The precise function of changes in [Ca2+]cyt is not yet known but might form a central part of a fine-tuned response to CLE40 peptide that serves to integrate root meristem growth with stem cell fate decisions and initiation of lateral root primordia.
CRIS-Team WoS Importer:2021-12-17